Factors Affecting Share Price of Nepalese Non-Life Insurance Companies - Gautam, Anamol; Bista, Nar Bahadur (Nepalese Journal of Insurance and Social Security, 2019)
This study examines the factors affecting the share price of Nepalese non-life insurance companies. This study is based on secondary data of 15 non-life insurance companies with 105 observations for the period from the fiscal year 2011/12 to 2017/18. The result shows that firm size is positively related to market price of share and price earnings ratio. It indicates that larger firm size leads to increase in market price of share and price earnings ratio. However, the study shows that inflation is negatively related to market price of share and price earnings ratio. The study also shows that dividend per share and return on assets are negatively related to the market price of share and price earnings ratio. Similarly, earnings per share have negative relationship with market price of share and price earnings ratio. The study concludes that the increase in return on assets and earnings per shares do not explain the variation in stock price in Nepalese non-life insurance companies. Nepal is one of the emerging economy; the determinants identified will provide knowledge to the potential investors about the key factors affecting share prices in the country and accordingly assist them in optimizing their investment strategy. The knowledge of the factors and their possible impact on share prices is highly appreciable as it would help investors make wise investment decisions and enable firms to enhance their market value.